FENOMENA PENCATATAN PERKAWINAN BAGI JANDA DI KUA KECAMATAN TANAH TUMBUH KABUPATEN TANJUNG JABUNG DITINJAU DARI HUKUM KELUARGA - Nindi Aliska Nasution (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2023)
This article aims to find out the process of registering marriages for widows in Tanah Grow District, Tanjung Jabung Regency. Uniquely, what is used instead of the divorce certificate for the prospective bride and groom is a certificate from the Village Head as a document requirement for carrying out the marriage. Meanwhile, Article 6 paragraph 2 letter (f) explains explicitly that the marriage registration procedure for widows is "having a death certificate of the previous wife or husband or in the case of a divorce a divorce certificate (divorce certificate), for marriages for the second time or more" . From this article it can be understood that if a widow wants to get married and the marriage is to be registered, then it must fulfill the existing requirements, one of which is the existence of a divorce certificate issued by the Religious Court. The type of research used is juridical research or what is called field research, namely research carried out in certain places using a qualitative approach method. Meanwhile, the data sources used are primary and secondary. The data collection methods used were interviews, observation and documentation. The results of this research show that the reasons or considerations of the Tanjung Jabung District KUA Tanjung Jabung Regency for registering the marriage of a widowed woman without a divorce certificate are: the first husband had issued a divorce, which according to the KUA was valid to continue with the iddah period having ended. Meanwhile, the pillars and conditions of marriage according to fiqh have been fulfilled. However, the administrative requirements are insufficient, namely the lack of a divorce certificate from the local Religious Court, but the prospective bride and groom replace it with a certificate from the Village Head. In this way, the KUA is not legally prevented from marrying her because one condition is lacking, namely a divorce certificate. From the KUA's considerations or reasons for all these couples, it is clear that the KUA is essentially not implementing the statutory regulations completely, this is caused by various factors. The factors that caused the KUA to issue this letter were economic factors and educational factors, because the bride and groom were classified as underprivileged, especially considering that the level of education in general in the local community was still at elementary level.